Carbamate and Organophosphate Contamination in Soil, Rice, and Water Samples from Rice Paddy Fields in Nakhon Nayok Province - Sirikul Thummajitsakul; Hathaichanok Praditpol; Julaluck Poolaoi; Kun Silprasit (Applied Environmental Research, 2015)
This study purposes to determine pesticides of carbamate and organophosphate group found in soil, rice, and water samples from rice paddy fields in Village number (Moo) 4, Banpraw Sub-district, Banna District in Nakhon Nayok Province. The sampling sites were selected in 27 agricultural areas using Global Positioning System (GPS). It was found that 42.3 % of all surveyed farmers had used pesticides in their rice paddy fields between June 2014 to January 2015. Moreover, the soil ( =27), water (n=10) and rice (n=27) samples were tested using a GT test kit. This study reports that 77.78 %, 85.18 % and 70 % of soil, rice and water samples respectively were contaminated with carbamate and organophosphate pesticides. It demonstrated that more than 60 % of the collected samples were contaminated with the pesticides, at the significance level of (p = 0.001). Herbicides were most frequently used (62.20 %), followed by insecticides (26.83 %) and chemical control of plant diseases (10.98 %). Organophosphate group was an insecticide that mostly used up to 50 % of the total used. Therefore, the obtained data may be further applied to improve the natural environment and to programs for health promotion of farmers.